Analisis Laporan Triwulan Koperasi di Kabupaten Banyumas Berbasis Web - Muh Sofi'i; Joko Purnomo; Eldika Riza Rahmawan (LPPM STMIK Widya Utama, 2018)
The development of information technology has influenced the performance of all aspects of society. The cooperative office has also utilized information systems to facilitate operational processes in cooperatives such as cooperative data processing and quarterly report of cooperatives.The Banyumas Cooperative Office is one of the parties that began planning to use the information system to delivering of quarterly reports of cooperatives with web-based. This study aims to reduce the problems that occur in the BanyumasCooperative office, namelybin submitting quarterly report and monitoring the cooperative report. For this reason, the application design process is based on the correct software engineering. The method used to design the application quarterly in the waterfall method. This research report will only describe the activities in delivering the quarterly report of cooperatives from cooperatives in the Banyumas district. With this web application, it is expected that the administrative department of the cooperative can monitor the delivery of quarterly reports of cooperative wherever and whenever.